The effect of Nd 2 O 3 addition on superconducting and structural properties and activation energy calculation of Bi-2212 superconducting system - Öztürk, Özgür; Aşıkuzun, Elif; Coşkunyürek, Murat; Soylu, Nevin; Hancerlioğulları, Aybaba; Varilci, Ahmet; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2013)
The effect of Nd 2 O 3 addition on the micro-structural and the superconducting properties of Bi-2212 superconductor ceramics, prepared by solid state reaction method, was analyzed by performing X-ray diffraction (XRD), scanning electronic microscope (SEM), energy dispersive spectroscopy (EDS) and dc Resistivity (ρ-T) measurements. The magnetoresistivity of the samples was measured for different values of the applied magnetic field strengths (0–7 T). Also, the activation energies were calculated using the Arrhenius equation. According to these results, the T c offset value of the undoped sample was decreased from 79 to 42 K with the growth of magnetic field. In the same way, the activation energy (U o ) values were significantly diminished by the increasing of magnetic field. A similar situation was observed in other doped samples. Activation energy for 0.05 % Nd 2 O 3 doped sample under 7 T magnetic field was 550 J/mol the least. In addition, lattice parameter c, calculated by analysis of XRD data, was decreased with doping while lattice parameter a was increased. SEM analysis shows that particles were shrinking with the addition. When compared with other elements for EDS analyses, it was analyzed an important decrease in the percentage of Sr with the increasing of Nd contribution.